UPAYA PENINGKATAN HASIL BELAJAR SISWA DENGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN PEMELIHARAAN MESIN KENDARAAN RINGAN (PMKR) MATERI SISTEM KERJA ENGINE DI SMK MA’ARIF NU 1 BENER - Pambudi Dwi Septiawan; Dwi Jatmoko; Widiyatmoko (STKIP Subang, 2026)
This study aims to: (1) describe the implementation of interactive learning media in the Light Vehicle Engine Maintenance (PMKR) subject on engine working system material; and (2) determine the magnitude of improvement in student learning outcomes through its application in Class XI TKR at SMK Ma’arif NU 1 Bener. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, comprising two cycles each consisting of planning, action, observation, and reflection stages. The subjects were 31 Class XI TKR students in the 2025/2026 academic year. Data were collected through a 20-item multiple-choice cognitive test (pre-test and post-test) and structured observation sheets covering 27 teacher activity indicators and 21 student activity indicators. The interactive learning media featured a 4-stroke engine cycle animation, an interactive engine component exploration module, a valve mechanism comparison animation (SV, OHV, SOHC, DOHC), and an interactive quiz. Results showed that the class mean increased from 59.03 (pre-cycle) to 70.97 (Cycle I) and 82.26 (Cycle II), a total gain of 23.23 points. Classical completeness rose from 35.48% (11 students) to 64.52% (20 students) in Cycle I and 93.55% (29 students) in Cycle II, surpassing the 75% success indicator. Teacher activity compliance improved from 85.19% to 96.30%, and student activity from 80.95% to 95.24%. These results confirm that interactive learning media is an effective and innovative solution for improving student learning outcomes in abstract and dynamic vocational subject matter.